1999
DOI: 10.1002/(sici)1522-2683(19991001)20:14<2945::aid-elps2945>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic determination of cathepsin D activity using Oregon Green-labeled hemoglobin

Abstract: Cathepsin D is an aspartyl protease of lysosomal origin and functions in a variety of roles including protein turnover, catabolism of peptide hormones, antigen processing and presentation, and neoplastic disease. In breast cancer, the level of cathepsin D has been linked to metastasis and prognosis for survivability. Many of these studies concerning the role of cathepsin D in cancer have used immunological detection methods to determine the level of enzyme. These indirect methods to assess the cathepsin D leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These applications include analysis of chemokine stromal cell-derived factor-1 [181], soluble chromatin from chicken erythrocytes [182], jellyfish venom proteins [183], sialoglycoproteins [184], turkey egg ovalbumin glycoforms [57], cathepsin D [185], bovine collagens [116], fluorescent adduct formed in vivo in collagen [71], caseinoglycomacropeptide in cosmetic lotions [186], polyethylene glycol-modified proteins (including hemoglobin as a potential blood substitute) [187], salmon calcitonin [188], ribonuclease and lysozyme [189], further transmembrane serine receptor [190], salivary a-amylase [191], outer membrane proteins from Proteus penneri [192], granulocyte colonystimulating factor [193], insulin antibodies [194], staphylococcal enterotoxin A [195], green fluorescent proteins in human embryonic kidney cells [196], peroxidase:antiperoxidase immune complexes [197], a(2u)-globulin in rat kidney cytosol [198], histone H1 variants [50], dilute proteins in formulations containing interfering excipients [199], subviral particles of human rhinovirus serotype 2 [200], seed 2S albumins [201], mutant a-and b-globulin chains [202], abnormal prion proteins [203] proteins interacting with DNA [204], alkaline phosphatase inhibited by theophylline [205], proteins in single cells [70], determination of Src kinase and kinase C activity [206], and bilirubin oxidase activity [207].…”
Section: Other Proteinsmentioning
confidence: 99%
“…These applications include analysis of chemokine stromal cell-derived factor-1 [181], soluble chromatin from chicken erythrocytes [182], jellyfish venom proteins [183], sialoglycoproteins [184], turkey egg ovalbumin glycoforms [57], cathepsin D [185], bovine collagens [116], fluorescent adduct formed in vivo in collagen [71], caseinoglycomacropeptide in cosmetic lotions [186], polyethylene glycol-modified proteins (including hemoglobin as a potential blood substitute) [187], salmon calcitonin [188], ribonuclease and lysozyme [189], further transmembrane serine receptor [190], salivary a-amylase [191], outer membrane proteins from Proteus penneri [192], granulocyte colonystimulating factor [193], insulin antibodies [194], staphylococcal enterotoxin A [195], green fluorescent proteins in human embryonic kidney cells [196], peroxidase:antiperoxidase immune complexes [197], a(2u)-globulin in rat kidney cytosol [198], histone H1 variants [50], dilute proteins in formulations containing interfering excipients [199], subviral particles of human rhinovirus serotype 2 [200], seed 2S albumins [201], mutant a-and b-globulin chains [202], abnormal prion proteins [203] proteins interacting with DNA [204], alkaline phosphatase inhibited by theophylline [205], proteins in single cells [70], determination of Src kinase and kinase C activity [206], and bilirubin oxidase activity [207].…”
Section: Other Proteinsmentioning
confidence: 99%
“…Figure 1 illustrates the typical outcome of an off-line MEKCbased enzyme assay using direct UV detection. The other popular detection technique is laser-induced fluorescence (LIF) with fluorescently-labeled substrates [28,31,32,34,44,45,64]. This technique is particularly advantageous in studies in which very small amounts of substrates or products are to be detected, because the detection limits of the LIF technique are often comparable with those of mass spectrometric methods.…”
Section: Mekcmentioning
confidence: 99%
“…Recent advances in CE have indicated that this technique has become the method of choice for determining numerous proteolytic activities in vitro and in vivo [18,19,21,[26][27][28]. To investigate whether the applicability of CE in free solution or MEKC can be further extended to measure TPP-I activity, human skin fibroblasts cultures were considered as a source of this proteinase.…”
Section: Determination Of Tpp-i Activity On Fibroblasts Of Healthy Sumentioning
confidence: 99%